PROFILE CONDITIONS AND ATHLETES PSHYIKIS SILAT PON RIAU YEAR 2016 - Aref Vai (FKIP Universitas Islam Indragiri, 2017)
To reach this achievement and meet the target in the National Sports Week (PON) XIX September 2016 in the West Java has been the preparations made athlete Riau and the Provincial Board sports, particularly at branch pencak silat martial arts. Further medical tests and physical athlete PON has also been done as well as he had done a training camp. From the research results can be seen that the level of physical condition of athletes silat team average PON Riau included in the category of less, nine athletes or 64.29% .of the 14 athletes who took the tests physical condition. Data obtained from tests and measurements performed by silat athletes from 11 types of physical kondidi tests. The result showed that of the 11 kinds of tests measuring physical conditions, the result for the test just WBR and Split are all athletes made it into the excellent category. While in many other physical conditions test the average entry in the category of moderate and less. While the level of keaadan physkis silat athletes Riau PON team average in the high category. This can be seen from the percentage that appears each indicator based on the processed data. To indicator of fatigue, the atmosphere of anger, depression, tension, confused atmosphere, if not controlled will have an impact on the appearance of athletes, although the indicators feeling prepared and confident high enough.